Hybrid process chains combining metal additive manufacturing and forming – A review - Hafenecker, Jan; Bartels, Dominic; Kuball, Clara-Maria; Kreß, Maximilian; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (CIRP Journal of Manufacturing Science and Technology, 2023)
Mass production of customized parts using conventional manufacturing technologies is challenging. The increasing use of hybrid approaches is a promising way to address mass customization. Due to the widespread use of the term hybrid in manufacturing technologies, the amount of literature is increasing dramatically. Therefore, this paper aims to provide an overview of the current state of the art on the combination of additive manufacturing (AM) and metal forming. First, the term hybrid is classified, followed by examples of hybrid AM. The focus of this paper is on the combination of either sheet metal forming or bulk metal forming with either powder bed fusion or directed energy deposition. Examples of both sequences - AM before or after forming - are presented and analyzed for their potential use in hybrid parts. From the selected literature, the possibilities of this approach are derived as well as the ongoing need for future research. AM offers great potential for adjusting the microstructure and resulting material properties to improve formability. Furthermore, forming operations need to be adapted to the different material properties found in hybrid part
Keywords: Hybrid manufacturing Hybrid processes Hybrid parts Additive manufacturing Sheet metal forming Bulk metal forming Review paper